Phoretic uropodine mites (Acari: Mesostigmata) associated with the red palm weevil, Rhynchophorus ferrugineus (Coleoptera: Curculionidae) in Iran - V.R. Farmahiny Farahani; A. Ahadiyat; P. Mašán; M.A. Dehvari (Journal of Entomological and Acarological Research, 2016)
During an investigation on phoretic mite associates of the red palm weevil, Rhynchophorus ferrugineus, in Sistan and Balouchestan Province of Iran, two uropodine species were collected and identified as Centrouropoda almerodai (Uropodidae) and Uroobovella marginata (Dinychidae). This is the first record of the genus Centrouropoda from Iran and the first record of phoretic mites associated with this weevil from the country.